A Single-Surgeon Retrospective and Preliminary Evaluation of the Safety and Effectiveness of the Penuma Silicone Sleeve Implant for Elective Cosmetic Correction of the Flaccid Penis. Issue 9 (23rd August 2018) - Elist, James J.; Valenzuela, Robert; Hillelsohn, Joel; Feng, Tom; Hosseini, Alireza
Abstract: Background: Silicone blocks and sleeves are simple devices used in cosmetic surgery. They are generally viewed as safe and effective; however, there is little information on their use in the penis. Aim: This study evaluates a large single-surgeon series using a novel silicone sleeve penile implant (Penuma) to cosmetically correct the flaccid penis. Methods: 526 patients underwent elective cosmetic penile surgery using a silicone sleeve penile implant between 2009 and 2014. Institutional Review Board approval was obtained for a retrospective analysis, and study consent was obtained from 400 patients. Penile circumference was measured before surgery, immediately after surgery, and 30–90 days after the implant surgery. Using the nonvalidated Augmentation Phalloplasty Patient Selection and Satisfaction Inventory (APPSSI), changes in self-confidence, self-esteem, and satisfaction scores were assayed 6–8 weeks postoperatively. Scores were again assayed 2–6 years postoperatively in 77% of patients. The questionnaires rated patient self-confidence, self-esteem, and satisfaction as very low, low, medium, high, or very high. Main Outcome Measure: Outcomes include changes in penile measurements; changes in APPSSI satisfaction, self-confidence, and self-esteem scores; and incidences of adverse events. Results: In the 400 patients, the implantation of the Penuma silicone implant increased midshaft circumference from an average of 8.5 ± 1.2 cm to 13.4 ± 1.9 cm (56.7% increase; P < .001). A 2-category improvement in self-confidence and self-esteem was noted in 83% of patients 6–8 weeks postoperatively. On long-term follow-up (2–6 years; mean 4 years), 72% patients remained improved (2-category improvement in APPSSI scoring), and 81% of subjects reported "high" or "very high" levels of satisfaction. The most frequently reported postoperative complications were seroma (4.8%), scar formation (4.5%), and infection (3.3%). No patients reported any changes in sexual function, erections, or ejaculation. 3% experienced adverse events necessitating device removal. Clinical Implications: The Penuma silicone implant can help patients cosmetically correct the penis with increased flaccid penile girth and achieve enhanced self-confidence and self-esteem over the short- and long term. Strengths and Limitations: Strengths include the large number of subjects (400 men) and the long-term follow-up period (2–6 years). Limitations include the retrospective and single-surgeon (inventor) nature of the study; the presence of 126 non-consenting subjects, potentially impacting the complication rate; and the APPSSI's lack of validation. Conclusion: Retrospective analysis of 400 men electing to have penile cosmetic correction with the Penuma device demonstrates improvements in girth (56.7% increase) and high and sustained patient satisfaction, self-confidence, and self-esteem with minimal and manageable adverse events.